The Role of PTHLH in Ovarian Follicle Selection, Its Transcriptional Regulation and Genetic Effects on Egg Laying Traits in Hens - Guo, Xiaoli; Wang, Yiya; Chen, Qiuyue; Yuan, Zhenjie; Chen, Yuxia; Guo, Miao; Kang, Li; Sun, Yi; Jiang, Yunliang (Frontiers in Genetics, 2019)
In hens, follicle selection is an important process affecting egg laying traits. This study investigated the role of parathyroid hormone-like hormone (PTHLH) in chicken follicle selection, its transcriptional regulation and genetic effects on egg laying traits. PTHLH and its receptor PTH1R were mainly expressed in follicles of 6-8 mm in diameter, exhibits differential expression pattern in the theca and granulosa cells of pre- and hierarchal follicles. PTHLH stimulates the proliferation of follicular granulosa and theca cells, the expression of StAR and CYP11A1 mRNA and the production of progesteron (P4) in pre-hierarchal follicles. Treatment with FSH increased PTHLH mRNA expression in the theca and granulosa cells of pre- and hierarchal follicles. Two critical regions regulating chicken PTHLH transcription were revealed, each of which harbored a SNP:C>T (rs72520524) for AP-1 and a SNP: A>G (rs72518862). Hens with diplotype AC/GT were younger at first laying and laid more eggs at 32 weeks. The haplotype (G−1827-T−165) with double mutations had the greatest promoter activity of chicken PTHLH transcription. Collectively, PTHLH plays an important role in chicken follicle selection by stimulating cell proliferation and steroidogenesis. Polymorphisms in chicken PTHLH promoter region are associated with egg laying traits by affecting the binding of transcription factor AP-1.